Pengaruh Kemudahan Dan Keamanan Terhadap Kepuasan Karyawan PT. Bridgestone Sumatra Rubber Estate (BSRE) Dalam Menggunakan Fitur Bsi Electronic - Siti Nurkhalifah; Mutiah Khaira Sihotang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of convenience and security on employee satisfaction of PT Bridgestone Sumatra Rubber Estate (BSRE) in using the BSI Electronic feature. This research is a type of quantitative research. The data collection method uses a questionnaire by distributing questionnaires and is measured using a Likert scale. The sampling technique used purposive sampling method with 98 respondents. The results of the partial test (t test) and (f test) show that convenience and security have a significant positive effect on the satisfaction of PT Bridgestone Sumatra Rubber Estate (BSRE) employees in using the BSI Electronic feature. Based on the results of the study, it can be concluded that the satisfaction of PT Bridgestone Sumatra Rubber Estate (BSRE) employees in using the BSI Electronic feature is influenced by the convenience and security that are well perceived by users. Keywords: Convenience, Security, Employee Satisfaction, BSI Electronic